Familial non-obese idiopathic intracranial hypertension - Raed Behbehani; Abdullah Ali; Ashref J. Al-Mousa; Sarah N. Albuloushi (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To report a series of cases of non-obese familial idiopathic intracranial hypertension. Observation: One father and three offsprings (two brothers and one sister) with idiopathic intracranial hypertension and different phenotypic presentations. Conclusion and Importance: Familial idiopathic intracranial hypertension may underrecognized and may not be associated with obesity. Symptomatic family members may need to be screened for IIH in some cases.